Estimation of long-run relationship of inflation (CPI & WPI), and oil prices with KSE-100 index: evidence from Johansen multivariate cointegration approach - Raheem Ahmed, Rizwan; Vveinhardt, Jolita; Štreimikienė, Dalia; Ghauri, Saghir Pervaiz; Ahmad, Nawaz (Technological and Economic Development of Economy, 2017)
This research is an attempt to framework the applied strides to evaluate the long run relationship among commonly used inflation proxies induces such as, wholesale price index (WPI) and consumer price index (CPI), and crude oil price (COP) with KSE100 index returns. In this research we used monthly data for the time period from July 1995 to June 2016, and thus, in this way total 252 observations have been considered. Time series have been made stationary by applying ADF and PP tests at first difference. Johansen multivariate conintegration approach was used to test the long-term association amongst the considered macroeconomic variables. The results indicated that CPI and COP significantly affect KSE100 index returns that indicated CPI along with COP have foreseen power to impact KSE100 index. In contrary, the results of WPI and COP do not have long run relationship with KSE100 index in case of Pakistani economy. Results of variance decomposition exhibited that the index of LKSE100 was realistically rarer exogenous in connection to distinctive factors, as around 92.31% of its variation was explained due to its own specific shocks. It is concluded that CPI and COP can impact the KSE100 index returns. It is confirmed by the results of impulse response function that there is a positive and long run relationship between KSE100 returns and consumer price index (proxy of inflation) and international crude oil prices.